Promosi Kuliner Jepang Melalui Media Sosial Sebagai Bentuk Diplomasi Publik : Studi Facebook Kedutaan Besar Jepang di Indonesia - Wa Ode Jumiati Ramadhan; Faturachman Alputra Sudirman; Saidin Saidin; Fera Tri Susilawaty (Laboratorium Ilmu Komunikasi, Fakultas Ilmu Sosial dan Ilmu Politik (FISIP) Universitas Ha, 2020)
This study discusses the Japanese culinary promotion through social media Facebook Japanese Embassy in Indonesia as a form of public diplomacy. The method used in this research is descriptive qualitative by collecting data used interviews and documentation. Based on public diplomacy from Kelley (2009) to analyze aspects of information, influence, and involvement. The results of the study show that the Japanese Embassy in Indonesia uses social media such as Facebook to promote culinarily. The promotion in social media is an effective way considering that Indonesia is one of the biggest users of social media in the world, it is also able to provide the understanding and a good image for Japan by the public Social media users in Indonesia. This is seen from the number of followers, likes, and positive comments on various Facebook admin posts of the Japanese embassy in Indonesia. The Japanese government develops and implements multiple public diplomacy activities in Indonesia to strengthen long-term relations for the two countries.Keywords: Media; Social; Diplomacy; Culinary; Japan